Where all the rivers flow west: Maps, abstraction and change in the Papua New Guinea lowlands - Dwyer, Peter D. (The Australian journal of anthropology, 2014)
‘Abstraction’ has been often identified as a key element in social change. Analyses, however, have often conflated the ideas of abstraction as ‘object’ and as ‘process’. This paper discusses two maps drawn by or on behalf of Kubo men, of the interior lowlands of southern Papua New Guinea. They were drawn in the context of recent exposure to a vast Liquefied Natural Gas project initiated on the land of their neighbours and both, as abstractions from new observations and experiences, were intended as assertions of rights to land. They derived, however, from entirely different logics: one more compatible with ‘Western’ understandings of ownership, the other more in keeping with earlier Kubo understandings of belonging. By reference to these maps, we consider the role of abstraction in social change and argue that while, as object, abstraction is relative as a process it is universal.